Pharmacokinetics and pharmacodynamics integration of danofloxacin against Eschrichia coli in piglet ileum ultrafiltration probe model - Yuqi Yang (Nature Portfolio, 2021)
Abstract Improper use of antibiotics results in poor treatment and severe bacterial resistance. In this study, ultrafiltration probes were successfully placed in the ileum of piglets with the aid of anesthetic. After the fluoroquinolone antimicrobial drug danofloxacin (DAN) was intramuscularly administered, blood and ileum ultrafiltrate were collected at different time points and then determined by High Performance Liquid Chromatography (HPLC). Pharmacokinetics (PK) parameters for plasma and ileum ultrafiltrate were calculated by WinNonlin software. The DAN concentration in ileum ultrafiltrate was much higher than that in plasma during the period 1.2–48 h. The DAN concentration in plasma reached its maximum at 1.10 ± 0.03 h, but reached at 6.00 ± 0.00 h in the ileum ultrafiltrate. The mean Cmax of the ileum is 13.59 times that of plasma. The elimination half-life (T1/2β) in the ileum ultrafiltrate (6.84 ± 1.49 h) was shorter than those in plasma (7.58 ± 3.20 h). The MIC, MBC and MPC of DAN in MH broth against Escherichia coli (O158) were 0.5 µg/mL, 0.5 µg/mL and 4 µg/mL, respectively. Both in vitro and ex vivo kill curves indicated that the killing mechanism of DAN against E. coli is concentration-dependent. The AUC/MPC ratio is 21.33 ± 2.14. Mean PK/PD index (AUC24h/MIC) for ileum ultrafiltrate that achieved bacteriostatic, bactericidal, and eradication were 99.85, 155.57, and 218.02 h, respectively. Three different dosages (1.49 mg/kg, 2.42 mg/kg, and 3.24 mg/kg) were calculated respectively based on AUC24h/MIC ratio above, which might provide a novel approach to the rational design of dosage schedules.